Comparative analysis: QOL in breast cancer patients before and during the COVID-19 pandemic - Pinholato, Letícia Araujo; Pupim, Maria Clara Santos; Herrera, Ana Cristina da Silva do Amaral; Oliveira, Carlos Eduardo Coral de (Mastology, 2021)
Introduction: The 2019 outbreak of coronavirus disease (COVID-19) posed unprecedented challenges of emotional matter for women diagnosed with breast cancer. This research aimed to compare the quality of life of patients who were diagnosed with breast cancer from 2014 to 2019, and patients who were diagnosed during the COVID-19 pandemic, from January to August 2020. Methods: A cross-sectional study was performed, including patients with breast cancer, associated or not with chronic pathologies, with no psychiatric disorders, aged over 18 years. The questionnaire developed by the European Organisation for Research and Treatment of Cancer (EORTC-C30) version 3.0 was used for the comparative analysis of quality of life. The study population consisted of 185 women, of which 43.2% (n = 80) were previously diagnosed and 56.7% (n = 105) were diagnosed during the pandemic, with a median age of 45 years (IQ = 15). Results: The EORTC-C30 quality of life score remained the same for both groups (33.33; 33.33). There was a decrease in the scores on the emotional (58; 50) and physical (60; 40) scales of patients diagnosed during the pandemic. Conclusions: Future longitudinal research should contribute to the understanding of the long-term effects of COVID-19 on the psychological health of patients with breast cancer.